Strategi Start-Up Produksi Biogas Dari Vinasse: Transisi Operasi dari Kotoran Sapi ke Vinasse - Rahmanta, Anugrah Perdana (ECOTAS, 2025)
Vinasse utilization as biogas forming substrate requires special handling because of it’s acidic state which is inhibitor to methanogens. At start-up, the performance of microbial group should be in state of equilibrium between methanogens and non-methanogens. This is attempted by adding inhibitor substrates incrementally. Start-up conduct in semi continue process with vinasse dry base composition 0% (S0), 50% (S1), 75% (S2), 90% (S3) up to 100% (S4). Biodigester loading rate is 40 kg/(m3/hari) with 8 litre effective slurry volume. Substrat is fed at 6,5% TS. The best pH stability obtained on S2 feed composition which is 6.3 for eleven consecutive days.This reflects the balance of methanogen and non-methanogenic microbes performance. The highest average daily biogas production was achieved at feed composition S3 of 3780mL even though the average pH tended to decrease to 6.18. At S4, pH and average biogas volume is decreased significanly to 5.9 and 1932mL.